(untitled) (Environment & Health, 2021)
For the effective and safe implementation of quarantine measures for the prevention of infectious diseases, it is necessary to a create the conditions for the maintenance of physical and mental health of the population, especially of the children and adolescents, the most vulnerable part of it. The monitoring of quarantine conditions, as well as a lifestyle of children with the identification of possible negative factors affecting the health of schoolchildren, is a prerequisite of it. Objective: We assessed the living conditions of school-age children during the COVID-19 pandemic lockdown. Materials and methods: We analyzed the results of the online survey of the parents of 920 children and adolescents from all regions of Ukraine (497 boys and 432 girls). All respondents signed informed consent. Data were collected from April 17 to June 5, 2020. We applied STATISTICA 8.0 for statistical analysis. Results: Only (59.4±1.7)% of urban and (33.1±4.3)% of rural families with school-age children adhered to quarantine rules (p